Impact of a Novel Insulin Management Service on Non-insulin Pharmaceutical Expenses - John E. Schneider; Anjani Parikh; Ivana Stojanovic (Journal of Health Economics and Outcomes Research)
**Background:** Studies have shown that improvements in glycemic control are associated with avoidance or delayed onset of diabetes complications, improvements in health-related quality of life, and reductions in diabetes-related health care costs. Clinical practice guidelines recommend maintaining a hemoglobin A1c (HbA1c) level less than 7%, but among type 2 diabetes patients using insulin, two-thirds have HbA1c above 7% and one-third have HbA1c above 9%.